Comparison between Viscosity and Surface Tension of Polyvinylpyrrolidone/ Silver Nanoparticle (PVP/ AgNP) Solutions and Polyethylene Glycol/ Silver Nanoparticle (PEG/ AgNP) Solutions - Elgheryani, Najla (Jordan Journal of Physics, 2025)
In the present study, viscosity and surface tension of Polyvinylpyrrolidone (PVP) solutions and Polyethylene glycol (PEG) solutions in water and nitric acid with different concentrations (0.0, 0.2, 0.4, 0.6, 0.8 and 1.0 %) of silver nanoparticles have been measured. However, the relative viscosity of PVP/ AgNP solutions increased from 2.245 to 2.585 and the relative viscosity of PEG / AgNP solutions increased from 1.150 to 1.204. Viscosity is a significant parameter during the electrospinning process. While the surface tension of the PVP/ AgNP solutions has changed from 0.052 Nm-1 to 1.46 Nm-1, it has changed from 0.063 Nm-1 to 0.160 Nm-1 for PEG / AgNP solutions. In this paper, attempts were made to obtain improvements to the properties of samples by comparing them with the pure samples of polymers. I think that there are personal errors in the measurements. These results can be used in medical, industrial applications and in scientific studies. Keywords: Polyvinylpyrrolidone (PVP), Polyethylene glycol (PEG), Silver nanoparticles (AgNPs), Viscosity (η), Surface tension (γ).